SOSIALISASI DAN EDUKASI FISIOTERAPI KEPADA MASYARAKAT MELALUI KEGIATAN CAR FREE DAY KABUPATEN KLATEN - Luklukaningsih, Zuyina; Yunitasari, Rima; Uningowati, Dwi Wahyuni; Setyaningtyas, Anna Febrianty; Indrayanto, Bayu; Susena, Danang; Sukini (LPPM Universitas Widya Dharma Klaten, 2023)
The objectives of the socialization and education of physiotherapy to the community through car free day activities in Klaten Regency are to: (1) socialize and introduce the Physiotherapy Study Program to the people of Klaten; (2) free physiotherapy services for the people of Klaten; and (3) physiotherapy training program education for the people of Klaten. The expected benefits of this community service activity are that the community knows the Physiotherapy Study Program and subsequently interested in taking part in physiotherapy education. It also helps people who are injured and has joint disease. Encouraging community members to undergo physiotherapy training in order to maintain and improve health. The method used in this service is the lecture method, question and answer, free checks (tension, pulse and temperature), Infra Red irradiation, supporting, and physiotherapy exercises.